2006
DOI: 10.1159/000090949
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Endothelial Cell Activation Increases Angiogenesis: Evidence for the Direct Role of Endothelium Linking Angiogenesis and Inflammation

Abstract: There is increasing evidence that chronic inflammation is tightly linked to diseases associated with endothelial dysfunction, including the induction of aberrant angiogenesis. While leukocytes have been described as mediators of inflammation-associated angiogenesis, the effects of direct chronic endothelial activation have not been addressed in this context. Using an uncleavable mutant of the transmembrane form of tumor necrosis factor-α (TNF-α), we have established models of stable TNF-α expression in endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 81 publications
3
74
0
4
Order By: Relevance
“…Consistent with this observation, our data showed an association of angiogenesis with MDSC accumulation in tmTNFa-or sTNF-a-expressing tumors. Although tmTNF-a expression has been shown to be upregulated in the tumor endothelium (54) and play an angiogenic role (55), it is possible that tmTNF-a may be a factor in tumor microenvironment that would facilitate MDSCdependent tumor angiogenesis. Briefly, our in vivo data indicated again that tmTNF-a plays an important role in the activation of MDSCs, and thus promotes tumor immune escape, one of the mechanisms involved in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this observation, our data showed an association of angiogenesis with MDSC accumulation in tmTNFa-or sTNF-a-expressing tumors. Although tmTNF-a expression has been shown to be upregulated in the tumor endothelium (54) and play an angiogenic role (55), it is possible that tmTNF-a may be a factor in tumor microenvironment that would facilitate MDSCdependent tumor angiogenesis. Briefly, our in vivo data indicated again that tmTNF-a plays an important role in the activation of MDSCs, and thus promotes tumor immune escape, one of the mechanisms involved in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that EC-specific transgenic mice expressing a membrane-bound TNF (mtTNF, a strong activator of TNFR2 in vivo) induced constitutive EC activation and inflammatory angiogenesis. 41 The role of TNFR2 activation in these mice has not been determined. Our results showed that TNFR2 signaling is specifically activated in vascular ECs in ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is further supported by analysis of the Tie2-tmTNFα mice. In these mice, endothelial cells exhibit a chronic activated phenotype as result of endothelial-specific constitutive expression of the TNFα membranebound form [29,30] and not in response to exogenous TNFα. As a result of endothelial cell activation, we found that J2 expression was upregulated in BM endothelial cells and that it correlated with increased Notch activation on Lin − Sca + Kit + hematopoietic progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Hes5-GFP mice were BAC transgenics from the NIDS GENSAT project (Rockefeller University, www.gensat.org). Tie2-tmTNFα transgenic mice and WT non transgenic littermates were described in [29,30]. Mice were matched for gender and analyzed at 4-5 weeks of age.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation